The Correlation between LGBTQ Tolerance and Economic Development in Europe - Tarnóczi, Tamara Dóra (International Journal of Engineering and Management Sciences, 2022)
This study analyses the relationship between LGBTQ tolerance and economic development. It uses various indices measuring tolerance and economic data of 48 European countries. Based on previous literature I outlined how economic progress is supposed to have an impact on the social inclusion of marginalised groups. Also, a number of empirical reports are cited providing substantial evidence that tolerance can too shape economic performance. The main aim of this paper is to confirm that these findings in fact hold water in Europe. Having examined the regression analysis of GDP per capita and tolerance, as well as HDI and tolerance, I found that the modernisation theory proved valid on my sample. The other component of my analysis focusing on the sway of social inclusion over FDI showed that more tolerant states attract more foreign capital. These results led me to believe that economic progress and LGBTQ inclusion are interrelated, thus the latter should be considered upon forming policy.